First virtual endocasts of adapiform primates. Issue 99 (October 2016) - Harrington, Arianna R.; Silcox, Mary T.; Yapuncich, Gabriel S.; Boyer, Doug M.; Bloch, Jonathan I.
Abstract: Well-preserved crania of notharctine adapiforms from the Eocene of North America provide the best direct evidence available for inferring neuroanatomy and encephalization in early euprimates (crown primates). Virtual endocasts of the notharctines Notharctus tenebrosus ( n = 3) and Smilodectes gracilis ( n = 4) from the middle Eocene Bridger formation of Wyoming, and the late Eocene European adapid adapiform Adapis parisiensis ( n = 1), were reconstructed from high-resolution X-ray computed tomography (CT) data. While the three species share many neuroanatomical similarities differentiating them from plesiadapiforms (stem primates) and extant euprimates, our sample of N. tenebrosus displays more variation than that of S. gracilis, possibly related to differences in the patterns of cranial sexual dimorphism or within-lineage evolution. Body masses predicted from associated teeth suggest that N. tenebrosus was larger and had a lower encephalization quotient (EQ) than S. gracilis, despite their close relationship and similar inferred ecologies. Meanwhile, body masses predicted from cranial length of the same specimens suggest that the two species were more similar, with overlapping body mass and EQ, although S. gracilis exhibits a range of EQs shifted upwards relative to that of N. tenebrosus . While associated data from other parts of the skeleton are mostly lacking for specimens included in this study, measurements for unassociated postcrania attributed to these species yield body mass and EQ estimates that are also more similar to each other than those based on teeth. Regardless of the body mass prediction method used, results suggest that the average EQ of adapiforms was similar to that of plesiadapiforms, only overlapped the lower quadrant for the range of extant strepsirrhines, and did not overlap with the range of extant haplorhines. However, structural changes evident in these endocasts suggest that early euprimates relied more on vision than olfaction relative to plesiadapiforms, despite having relatively small endocranial volumes compared to extant taxa.